PENGARUH PERLAKUAN KOMPOS SAMPAH KOTA DAN KOMPOS RESIDU RUMAH TANGGA PADA TANAH TERHADAP KADAR Pb SERTA Cd TERSEDIA DAN PRODUKSI SAWI (Brasillia oleraceae L.) - Denny R. Siregar; Abdul Rauf; Lahuddin Musa (Jurnal Agroekoteknologi, 2014)
The effect of domestyc waste compost and residual of household waste compost for Pb and Cd andmustard (Brassica oleraceae L.) product.This research is done in the land of cassa room ofagricultural faculty and is analised central labor of agricultural faculty, North Sumatera University.The design of this research is arranged in non-factorial random design which is consisting of 9treatments with 3 replications. The treatmentis treatmentis M1 (100% Soil), M2 (75% Soil + 25%domestyc waste compost), M3 (50% Soil + 50 % domestyc waste compost), M4 (25 % Soil + 75 %domestyc waste compost), M5(75% Soil + 25 % residual of household waste compost), M6 (50%Soil + 50% residual of household waste compost), M7(25% % Soil + 75% residual of householdwaste compost), M8 (50 % domestyk waste compost + 50 residual of household waste compost),M9 (100 % residual of household waste compost). The result of this research is showed thatcomposing domestyc waste compost and residual of household waste compost and combination ofboth very significantly increased to increase pH soil, Pb, Cd soil and production of weigh themustard in a good treatment is M3 (50% Soil + 50% domestyc waste compost) is 142,47 g.Keywords : domestyc waste compost, residual of household waste compost, Pb and Cd soil andmustard